"How to Compare?" – On the Methodological State of Comparative Philosophy. Issue 7 (23rd July 2013) - Weber, Ralph
Abstract: From early on, comparative philosophy has had on offer a high variety of goals, approaches and methodologies. Such high variety is still today a trademark of the discipline, and it is not uncommon of representatives of one camp in comparative philosophy to think of those in other camps as not really being about 'comparative philosophy'. Much of the disagreement arguably has to do with methodological problems related to the concept of comparison and with the widely prevailing but unwarranted assumption that comparative philosophy should be about comparing 'culturally different philosophies'. This paper seeks to problematize this assumption by clarifying conceptually the notions of 'comparative philosophy' and of 'comparison', by showing the prevalence of the assumption in recent second‐order discussions of methodology in comparative philosophy and its restraining implications in a randomly selected contribution of 'Chinese philosophy'. At the end, a rallying call for a (self‐)critical comparative philosophy is issued.